2018
DOI: 10.1097/md.0000000000012006
|View full text |Cite
|
Sign up to set email alerts
|

EORTC risk tables are more suitable for Chinese patients with nonmuscle-invasive bladder cancer than AUA risk stratification

Abstract: Background:Patients with non-muscle-invasive bladder cancer (NMIBC) need accurate estimations of the risk of recurrence and progression. Physicians can offer individualized therapy after identifying high-risk tumors. In our study, we compared the applicability of European Organization for Research and Treatment of Cancer (EORTC) risk tables and American Urological Association (AUA) risk stratification in Chinese patients with NMIBC.Methods:We retrospectively studied 301 patients with NMIBC who underwent transu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Kaplan-Meier curves showed signi cant differences among the 2 RFS (P = 0.0362 < 0.05, logrank test) and 3 PFS (P = 0.0077 < 0.01, log-rank test) levels separately, demonstrating that EORTC risk scores is predictive to tumor recurrence and prognosis of MG patients. These results are consistent with previous research by Wang et al (20), who reported that EORTC risk scores were better for predicting recurrence and progression in Chinese patients with NMIBC. The results of our study showed that the short-term recurrence rate of bladder cancer is basically consistent with the EORTC system.…”
Section: Discussionsupporting
confidence: 93%
“…Kaplan-Meier curves showed signi cant differences among the 2 RFS (P = 0.0362 < 0.05, logrank test) and 3 PFS (P = 0.0077 < 0.01, log-rank test) levels separately, demonstrating that EORTC risk scores is predictive to tumor recurrence and prognosis of MG patients. These results are consistent with previous research by Wang et al (20), who reported that EORTC risk scores were better for predicting recurrence and progression in Chinese patients with NMIBC. The results of our study showed that the short-term recurrence rate of bladder cancer is basically consistent with the EORTC system.…”
Section: Discussionsupporting
confidence: 93%
“…by Shen et al [15] Our systematic analysis has also shown the inconsistency in reporting the validity of utilized stratification approaches. For example, very recent analysis of 301 patients by Wang et al [16] or the analysis of 1436 patients by Rieken et al [17] (e.g. in the group without immediate postoperative instillation of chemotherapy) could not be included in the review due to lack of c-index or AUCROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…BCG is a live-attenuated strain of Mycobacterium bovis that induces an immune response in the bladder when administered [7]. Although approximately 70% of patients with NMIBC achieve complete response (CR) with BCG therapy, many patients with high-risk disease do not maintain remission [8][9][10][11][12][13]. As many as 60% of patients can have disease recurrence within 1 year, increasing to 80% within 15 years [9,13].…”
mentioning
confidence: 99%
“…Although approximately 70% of patients with NMIBC achieve complete response (CR) with BCG therapy, many patients with high-risk disease do not maintain remission [8][9][10][11][12][13]. As many as 60% of patients can have disease recurrence within 1 year, increasing to 80% within 15 years [9,13]. In addition, within 5 years, up to approximately 20-40% of patients who experience BCG failure will also experience progression to muscle invasive disease [14][15][16][17] and approximately 6-15% of patients will have metastasis to the lymph nodes [18][19][20].…”
mentioning
confidence: 99%